ADMA reduction does not protect mice with streptozotocin-induced diabetes mellitus from development of diabetic nephropathy. (November 2017) - Rodionov, Roman N.; Heinrich, Annett; Brilloff, Silke; Jarzebska, Natalia; Martens-Lobenhoffer, Jens; Bode-Böger, Stefanie M.; Todorov, Vladimir T.; Hugo, Christian P.M.; Weiss, Norbert; Hohenstein, Bernd
Abstract: Background and aims: Cardiovascular disease is the major cause of morbidity and mortality in the world. Diabetes and its complications, such as diabetic nephropathy, dramatically increase cardiovascular risk. Association studies suggest that asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthases, plays a role in the pathogenesis of diabetic nephropathy. The major pathway of ADMA catabolism is hydrolysis by dimethylarginine dimethylaminohydrolase 1 (DDAH1). The goal of this study was to test the hypothesis that lowering ADMA by overexpression of DDAH1 protects from development of diabetic nephropathy. Methods: Diabetes was induced with streptozotocin (STZ) in wild type and DDAH1 transgenic mice. Healthy mice served as controls. Mice were sacrificed after 20 weeks of diabetes. ADMA levels were assessed by isotope-dilution tandem mass spectrometry, creatinine by standard laboratory methods and albumin by ELISA. Kidney tissues were stained for markers of glomerular cells, cell matrix, inflammation and cell proliferation. Results: STZ led to development of diabetes in all injected mice. Transgenic overexpression of DDAH1 led to a decrease in plasma ADMA levels in healthy animals. Diabetic state itself did not lead to elevation of plasma ADMA levels. Diabetic mice of both genotypes developed albuminuria (27 and 25 vs. 9 and 6 μg albumin/mg creatinine) ( p < 0.01). There were no changes in glomerular matrix expansion, podocyte injury, inflammatory or proliferative response. Conclusions: STZ-induced diabetes led to the development of early features of diabetic nephropathy. Overexpression of DDAH1 and lowering of systemic ADMA levels did not prevent these changes, indicating that ADMA is not the major mediator of the early diabetic changes reflected by this experimental model.